Clinical and Laboratory Characteristics of Viral Diarrhea in Children and Antiviral Therapy - E. V. Mikhailova; A. N. Danilov; D. Yu. Levin (Детские инфекции (Москва))
The article presents the clinical and laboratory features of the course of rotavirus and norovirus infections in children. We provide the clinical and laboratory rationale for application of antiviral drugs in children of 3 to7 years old at moderate to severe forms of viral diarrhea. We determined the effect of Arbidol on elimination of rotavirus in the acute period disease.